Cattle-oil palm integration – a viable strategy to increase Malaysian beef self-sufficiency and palm oil sustainability - Grinnell, Natascha A.; Linden, Aart van der; Azhar, Badrul; Nobilly, Frisco; Slingerland, Maja (Elsevier, 2022)
Palm oil production in Malaysia contributes significantly to the national economy, but its production has adverse effects on the environment. A solution to mitigate environmental impacts and increase resource use efficiency is integrating palm oil and beef cattle production. This can reduce deforestation, needs for grazing land, and reduce herbicide use in plantations when cattle graze the weeds. Integration is more complex if the plantation and cattle are owned by different parties, as plantation owners indicate they perceive little or no benefit from integration. As a result, plantation managers consider the undergrowth as weeds and do not aim at improving the nutritional quality and biomass. This disinterest may explain why the potential of the undergrowth as forage has been understudied. The first objective of this study was, therefore, to assess the nutritional quality of the undergrowth in an integrated oil palm-cattle system where cattle are owned by smallholder farmers. The second objective was to estimate to what extent the nutritional requirements of cattle grazing the undergrowth are met. Plant species composition was determined and biomass was measured in an oil palm plantation in Peninsular Malaysia. Furthermore, the cattle diet was estimated from observations during grazing and interviews with five smallholder farmers were conducted. The species with the highest biomass in the undergrowth were Ottochloa nodosa, Axonopus compressus, Cyrtococcum oxyphyllum, Arthraxon hispidus, and Adiantum latifolium. Cattle selected for the more nutritious species within the available biomass. The grass A. compressus (64 %) and pruned oil palm fronds (18%) made up most of the cattle's diet, and the leguminous cover crop Pueraria phaseoloides was preferred if present. The diet contained 151 g crude protein (CP) kg−1 DM, and the ME content was 7.5 MJ ME kg−1 DM. The nutritional quality was estimated to cover energy requirements of cattle for maintenance by 1.6 times, whereas it provided ample CP. These results suggest that energy requirements may not always be fully met. Energy deficiency could be mitigated by feeding cattle with palm kernel meal, an energy-rich by-product from palm kernel oil production. Cattle were kept at or above the recommended stocking density for Malaysian plantations (0.11 TLU ha−1). Our observations suggest that the carrying capacity of the undergrowth is higher than the recommended stocking density, which implies scope to increase stocking densities and beef production, thereby reducing the need for further deforestation. In conclusion, integrating palm oil and cattle production is a viable strategy for both smallholders and plantation management to increase resource use efficiency in plantations and beef self-sufficiency in Malaysia.